The Reality of the Use of ICT and their Pedagogical Mediation to Enrich English Classes - Chaves Carballo, Olga (2015)
The main objective of this paper is to identify and analyze the use of ICTs and the pedagogical mediation that professors of the English Department at the School of Literature and Language Sciences (ELCL) at Universidad Nacional (UNA) use to enhance their English classes. By complying with the quality standards of an accredited major by SINAES, professors of the English majors recognize the importance of being up-to-date when it comes to innovative strategies with the support of ICT. It is plausible that these state-of-the-art technologies promote learning through a series of virtual tools that foster the students’ learning styles, multiple intelligences, and special needs, in order to improve their academic performance. This study was carried out in February, 2015 with a sample of 27 professors who have shown an effort and interest in knowing how to implement the different technological resources in their classes. Moreover, the results of this study demonstrate that the School of Literature and Language Sciences has gone to great lengths to improve in this area by offering constant professional development activities on a regular basis.